Acaricidal activity of essential oils of Bursera graveolens (Kunth) Triana & Planch and Schinus molle L. on unengorged larvae of cattle tick Rhipicephalus (Boophilus) microplus (Acari:Ixodidae). Issue 4 (4th July 2017) - Rey-Valeirón, Catalina; Guzmán, Lucía; Saa, Luis Rodrigo; López-Vargas, Javier; Valarezo, Eduardo
Abstract: The use of bio-derivatives as acaricides would be an effective and safe method of tick control. The acaricidal effect of essential oils obtained from Bursera graveolens (Burseraceae) and Schinus molle (Anacardiaceae), traditionally used by indigenous Ecuadorian medicine as insecticides, was tested on larvae of cattle tick Rhipicephalus ( Boophilus ) microplus. Essential oils were obtained from mature fruits by hydrodistillation and analyzed by gas chromatography. The acaricidal activity of essential oils against larvae was measured by larval package test with six concentrations of each essential oil. In total, sixteen compounds were identified in B. graveolens and twenty-one in S. molle essential oil . The mortalities of larvae in assays conducted with B. graveolens essential oil ranked from 35.43 to 100%; in S. molle from 5.58 to 100%. The obtained results show a clear and promising acaricidal effect of both essential oils over larvae of R. (B.) microplus.